Intermetallic Compound (Volume II) - Ćwik, Jacek (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In modern society, the applications of new functional materials are diverse and countless. Intermetallics, namely, compounds formed by two or more metallic elements, are among the various novel and significant materials developments. Intermetallics have received considerable attention owing to their potential for various applications, such as permanent magnets, magneto-optical recording media, hydrogen storage and magnetocaloric materials, turbine blades, and in microelectronics. With a favorable combination of high strength, low density, and good corrosion resistance, intermetallics are specifically suited for applications at high temperatures and in adverse environments. They can also display desirable magnetic, superconducting, and chemical properties due to their strong internal order and mixed metallic and covalent or ionic bonding, respectively. This Special Issue "Intermetallic Compound (Volume II)" is launched to serve as a unique multidisciplinary forum covering broad aspects of the science, technology, and application of intermetallic compounds. Potential topics include but are not limited to: Synthesis of intermetallic compounds; Characteristics of structural properties; Type of intermetallic compounds; Unique properties; Applications.